(untitled) (International Journal of Engineering and Computer Science, 2015)
Database has been considered to be very important since a really long time and securing it now is of utmost importance-healthcare systems is very popular now but faces security constraints. The distributed m-healthcare systems allow significant patient treatment for medical consultation by sharing personal health information among healthcare providers. The important challenge is to ensure the security of the patient’s identity as well as the data. Patients can decide which physician can access their information by using threshold predicates. Based on this idea we are devising a new technique where the patient can self-control their data with different ways of security. The directly authorized physicians and the patient can respectively decipher the personal health information and/or verify and update patient’s health information at the click of a button.